2014
DOI: 10.1186/1757-2215-7-50
|View full text |Cite
|
Sign up to set email alerts
|

Changes in granulosa cells gene expression associated with growth, plateau and atretic phases in medium bovine follicles

Abstract: BackgroundThe objective of this study was to build the transcriptomic profile of granulosa cells originating from follicles 6 to 9 mm in diameter in dairy cattle using microarrays.MethodsGranulosa cells originating from three different phases of antral follicle growth were compared: growing (G), plateau (P) and atresia (A), as categorized by flow cytometry profiles of DNA. The growing and atretic conditions were each hybridized against the plateau condition as a reference in order to understand the specific bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 72 publications
4
42
0
Order By: Relevance
“…APP has been associated with mitochondrial dysfunction, which may compromise oocyte quality, fertilization, and development into viable offspring (26). Overexpression of MYC, in addition to causing ovarian cancer (30), affects follicle growth, oocyte quality, and embryo development (7,9). Decreased expression of PGR (progesterone receptor), known for its role in oocyte competence acquisition and ovulation (6), likely decreases oocyte quality.…”
Section: Discussionmentioning
confidence: 99%
“…APP has been associated with mitochondrial dysfunction, which may compromise oocyte quality, fertilization, and development into viable offspring (26). Overexpression of MYC, in addition to causing ovarian cancer (30), affects follicle growth, oocyte quality, and embryo development (7,9). Decreased expression of PGR (progesterone receptor), known for its role in oocyte competence acquisition and ovulation (6), likely decreases oocyte quality.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study on the transcriptomic profiles of granulosa cells revealed several genes linked to follicular development before establishment of dominance, and provided tools to classify medium-sized (6-9 mm) follicles in different growing phases [19]. …”
Section: Introductionmentioning
confidence: 99%
“…The gene expression in bovine granulosa cells collected from three different phases of follicle development was examined previously, and TP53 and SP1 were shown to be the main upstream factors between the growth and plateau phases [12]. In the comparison of oocytes with expanded cumulus cells and those with compact cumulus cells, expression of STAT3 was detected in oocytes associated with high developmental competence [13].…”
Section: Discussionmentioning
confidence: 99%